Identification of genes associated with litter size combining genomic approaches in Luzhong mutton sheep. (17th May 2021) - Tao, L.; He, X. Y.; Wang, F. Y.; Pan, L. X.; Wang, X. Y.; Gan, S. Q.; Di, R.; Chu, M. X.
Summary: Litter size is one of the most important reproductive traits of sheep, which has pronounced effects on the profit of husbandry enterprises and enthusiasm of breeders. Despite the importance of litter size, the underlying genetic mechanisms have not been entirely elucidated. Therefore, based on a high‐density SNP chip, genome‐wide comparative analysis was performed between two groups with different fecundity to reveal candidate genes linked to litter size via detection of homozygosity and selection signatures in Luzhong mutton sheep. Consequently, nine promising genes were identified from six runs of homozygosity islands, and functionally linked to reproduction ( ACTL7A, ACTL7B, and ELP1 ), embryonic development ( KLF5 and PIBF1 ), and cell cycle ( DACH1, BORA, DIS3, and MZT1 ). A total of 128 genes were observed under selection, of which HECW1 and HTR1E were related to total lambs born, GABRG3, LRP1B, and MACROD2 to teat number, and AGBL1 to reproductive seasonality. Additionally, the presence of inbreeding depression implies the urgency of reasonable mating system to increase litter size in the present herd. These findings provide a comprehensive insight to the genetic makeup of litter size, and also contribute to implementation of marker‐assisted selection in sheep.